Effect of Breadfruit Leaf Extract on Sperm Quality in Diabetic Male Wistar Rats - Rafi Ilmansyah; Ulya Hasna Khairunnisa; Cendikia Sengkalaning Pangrukti; Rifki Rizaldi; Rr Mahayu Dewi Ariani; Donna Hermawati; Eka Chandra Herlina; Acmad Zulfa Juniarto (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Diabetes mellitus can lead to various complications, one of the most devastating complications is infertility. Meanwhile, the antioxidant compounds of breadfruit leaves have been shown to help heal oxidative stress and therefore prevent infertility in diabetic patients. Therefore, this study aimed to determine the effect of breadfruit leaves in improving sperm quality parameters in male diabetic Wistar rats.Methods: In this study, twenty four male rats were used and were classified into four groups. Two of the four groups were alloxan-induced diabetics and were treated with a graded dose of breadfruit leaf extract. The two control groups received no therapy and the treatment was administered for 30 days. The rats were terminated after day 31 and sperm concentration, morphology, motility, and spermatogenesis were examined. Result: The results showed that breadfruit leaves increase sperm quality parameter levels compared to the control groups. The group that received a 400 mg/kg dose of breadfruit leaves showed the most significant improvement in terms of the level of sperm parameters compared to the other group that received a dose of 100 mg/kg breadfruit leaves. Conclusions: The protective effect of breadfruit leaves significantly reduced sperm damage caused by diabetes mellitus in Wistar Rats.